Characteristics of Lactobacillus strains isolated from Vietnamese patients with type 2 diabetes - Hung, Hoang The; Tu, Hoa Thi Minh; Uyen, Pham Thi Thu; Huyen, Le Thi Thanh; Hien, Vu Thi; Thu, Ha Thi; Duc, Le Hoang; Nam, Nguyen Trung; Nhung, Nguyen Thi Tuyet (Vietnam Journal of Biotechnology, 2022)
Many studies show that hyperglycemia can lead to injury to the intestinal mucosal barrier, increasing the likelihood of infection, leading to intestinal inflammation in people with type 2 diabetes. Recently, investigations indicate that the gut microbiome plays a very important role in this disease in which Lactobacillus in the gut has been shown to regulate glucose and lipid metabolism, improving oxidative stress, and inhibiting inflammatory responses. In this study, by the method of oriented isolation, the number of Lactobacillus bacteria in the subgroup of healthy people was determined to be (3,9 ± 1.2) x 103 CFU/g and in the group of diabetic patients was (2.7 ± 0.8) x 103 CFU/g. The study identified 17/68 selected Lactobacillus strains that were resistant to both Staphylococcus aureus ATCC13709 and Escherichia coli ATCC 11105. Moreover, these strains were also resistant to acid pH 2. Besides that, 16/17 strains tested were able to survive over 90% in 0.3% bile salt environment. Among the 17 strains studied, 3 strains of Lactobacillus 13, Lactobacillus 16, Lactobacillus 17 showed probiotic characteristics such as antibacterial ability, acid tolerance and bile salt tolerance. All three strains of Lactobacillus 13, Lactobacillus 16, and Lactobacillus 17 belong to species of Lactobacillus plantarum. This result makes a useful contribution to guide the application of Lactobacillus strain in creating dietary supplements for people with type 2 diabetes.